2017
DOI: 10.1017/s2040174417000071
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enteropathy is associated with cardiometabolic risk factors in Peruvian children

Abstract: Environmental enteropathy (EE) is a syndrome of altered small intestine structure and function hypothesized to be common among individuals lacking access to improved water and sanitation. There are plausible biological mechanisms, both inflammatory and non-inflammatory, by which EE may alter the cardiometabolic profile. Here, we test the hypothesis that EE is associated with the cardiometabolic profile among young children living in an environment of intense enteropathogen exposure. In total, 156 children part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 65 publications
(99 reference statements)
0
31
0
Order By: Relevance
“…No association between microbial translocation and permeability/absorption was observed in 2 studies [ 55 , 63 ], and 1 study observed conflicting results between the two domains [ 120 ]. Two studies did not report direct associations between permeability/absorption and microbial translocation [ 33 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No association between microbial translocation and permeability/absorption was observed in 2 studies [ 55 , 63 ], and 1 study observed conflicting results between the two domains [ 120 ]. Two studies did not report direct associations between permeability/absorption and microbial translocation [ 33 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, 4 studies found no association between microbial translocation and linear growth [ 55 , 99 , 107 , 122 ], and one study reported an unexpected positive association between microbial translocation and linear growth [ 63 ]. One study observed conflicting results between microbial translocation and linear growth [ 123 ], and 3 studies did not report associations [ 33 , 53 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations